Technical Optimization and Experimental Validation of Wall-Mounted Cylindrical Solar Cell in Urban Environments - Fumiki Tamura; Kento Honma; Shinji Yokogawa; Syuzi Hayase; Masaki Nakamura; Tomoyuki Hirami; Daisuke Hirotani; Yuya Sono; Toshihiro Takenoya; Daishiro Nomura; Takatoshi Nomura; Masahiro Hayashi (IEEE Access)
Cylindrical solar cells have omnidirectional light reception, excellent heat dissipation, and high wind resistance, making them suitable for application in solar power generation systems in urban environments. In this study, we conducted technical optimization and experimental verification of a cylindrical solar cell module installation on urban building walls. We performed illumination simulations by varying the wall orientation, reflectance, and distance between the module and the wall. We evaluated the effects on the light reception characteristics and power generation performance. Additionally, we verified the validity of the simulation results through actual power generation measurements of the cylindrical modules. The simulation results indicated that, under the evaluated conditions, the light reception increased under the white wall installation conditions. Moreover, the light-reception characteristics were further improved by setting the distance from the wall to 600 mm. When no wall was present, orienting the modules in an east-west direction (90°) was effective. Actual power generation measurements confirmed that the cylindrical solar cell modules exhibit increased power generation during morning and evening hours, demonstrating a stable performance in terms of daily cumulative power generation. Furthermore, sealing durability evaluations suggested that the modules possessed high environmental durability. These results show that cylindrical solar cells are technically feasible and reliable for the development of wall-mounted solar power generation systems suitable for urban spaces.